Drawbell drill and blast recovery at New Afton mine - Ierino, M.; Berg, A.; Martyniuk, E.; Yanagimura, Y. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
New Afton mine consists of 4 mining zones: Lift 1, B3, C-Zone, and East Extension. The C-Zone block cave is currently the only active mining area, with commercial production having begun in the fourth quarter of 2024. In block caving operations, drawbell construction is critical to production, allowing the flow of caved ore through drawpoints. During the C-Zone production ramp-up phase, open brows at drawpoints resulting from incomplete drawbell breakage were first identified. LiDAR scans and drone footage confirmed that the upper portion of drawbells were intact with no connection to the undercut. At the height of open drawpoint occurrences at the beginning of 2025, draw could not be achieved from approximately half of the drawbells following primary blasting. The high location of unfragmented drawbell material did not meet the criteria for standard hung-up drawbell treatment, requiring a recovery drill and blast approach. Experience in recovery drill and blast methods was limited to the undercut levels of Lift 1 and B3; therefore, the C-Zone drawbell recovery strategy was iterated throughout the process to optimise results. By the second quarter of 2025, 10 drawbells had successfully returned to daily draw using drill and blast recovery methods. This paper discusses the C-Zone drawbell recovery strategy and the revisions made to the drill and blast design and operational practices to improve future blast performance.